2002
DOI: 10.1093/rheumatology/41.1.14
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐delivered advice intervention can reduce chronic non‐steroidal anti‐inflammatory drug use in general practice: a randomized controlled trial

Abstract: Nurse-based intervention can reduce chronic NSAID usage and costs in primary care and would be cost-effective if maintained in the long term. This intervention package would be readily applicable in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…There is growing evidence to support the role of nurses and pharmacists in chronic pain management [7,8,9]. Pharmacist-led interventions have been shown to reduce pain intensity, improve physical functioning and reduce adverse events among chronic pain patients [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence to support the role of nurses and pharmacists in chronic pain management [7,8,9]. Pharmacist-led interventions have been shown to reduce pain intensity, improve physical functioning and reduce adverse events among chronic pain patients [7].…”
mentioning
confidence: 99%
“…Pharmacist-led interventions have been shown to reduce pain intensity, improve physical functioning and reduce adverse events among chronic pain patients [7]. Similarly, nurse-led interventions have been shown to reduce the chronic use of non-steroidal anti-inflammatory drugs (NSAIDs) [8], and improve physical functioning [9] and self-management skills.…”
mentioning
confidence: 99%
“…68 Importantly, this was not detrimental to the patients' symptoms, function, or quality of life. Such an intervention involving advice and, if needed, simple alternative non-drug and over the counter treatments, would be cost effective if continued long term.…”
Section: Safety and Costsmentioning
confidence: 94%
“…Such an intervention involving advice and, if needed, simple alternative non-drug and over the counter treatments, would be cost effective if continued long term. 68 March et al used "n of 1" trials to determine the comparative efficacy of paracetamol and oral NSAIDs within individual patients with OA. 69 As with later studies 7 8 15 they could not demonstrate clear overall superiority for NSAIDs, and at six months OA in almost half their patients was well controlled by paracetamol.…”
Section: Safety and Costsmentioning
confidence: 99%
“…The requirement to reduce NSAID usage in older OA patients has led to studies that have shown that nurseled education programmes and use of alternative simple nonpharmacological measures can greatly reduce chronic NSAID usage among OA patients in primary care with no detriment to the patients. 16 …”
Section: Oral Nsaidsmentioning
confidence: 99%